Effectiveness of Giving Red Guava Juice and Mung Bean on Hemoglobin Levels Among Post-Partum Mothers with Anemia - Angguniawati, Reni; Khairiah, Rahayu (STIKep PPNI Jawa Barat, 2024)
Aims: to determine the effectiveness of giving red guava juice and mung bean porridge to increase HB levels in postpartum women with anemia. Methods : The study was quasi-experimental, with a pretest-posttest design for two groups. The sample for this study consisted of all postpartum women who developed anemia between June and July 2023 at the Cikampek Health Center, which may be up to 40 participants. The sampling approach is complete sampling. Results : The red guava juice intervention group had an average HB level of 10.220 gr/dl pre-test and 12.460 gr/dl post-test. The green bean porridge intervention group had an average HB level of 10.230 gr/dl before testing and 12.440 gr/dl after testing. Giving red guava juice and mung bean porridge can successfully improve Hb levels in anemic postpartum women (p-value = 0.000). Conclusions : Red guava juice and mung bean porridge can significantly boost Hb levels in anemic postpartum women. It is believed that postpartum women who have anemia will take red guava juice and mung bean porridge as an alternative to prevent anemia.